Perancangan Interior Library Cafe di Surabaya - Yesika Hartanto Karjodihardjo; Stephanus P Honggowidjaja (Intra, 2015)
Interior planning of Library Café in Surabaya is a library facilitated with a café that provides information and learning facilities for young people. The purpose is to improve the culture of reading and to promote young people’s point of view about library as an open and comfortable learning facility. The facilities in library café, includes reading area, counter area, multipurpose room, staff and locker room, small groups and study space area, computer area, information and service area.The design concept theme is “Catchy and Homey”, where Catchy describes the characteristic of youth which are energetic, bold, cheerful, and fresh which is applied through pop arts style. Homey describes the comfortable feeling in space which is applied through modern contemporary style with simple design, the use of natural light, neutral color, and combination of modern and natural material based on function aspect.The design method used is “design thinking” method, consisting of 5 process, such as discovery (collecting data), interpretation (problem solving analysis), ideation (brainstorming), experimentation (design development), and evolution (final evaluation), whereas the result is manifested in presentation drawings and a 1:50 scaled miniature.